“There is no place on earth where women are freer”. Research notes on the tapadas limeñas as a bodily practice of female resistance in colonial Lima between the 16th and 19th centuries - Grandón Valenzuela, Débora (Re-presentaciones: Periodismo, comunicación y sociedad, 2022)
The tapada limeña was a clothing practice used by women in colonial Lima, between the end of the 16th century and the middle of the 19th century, which was subject to permanent censorship through a systematic agenda of “anti-covered” legislation throughout its almost 3 centuries of persistence. With the aim of recognizing in the tapadas limeñas a bodily practice of feminine resistance necessary to highlight in our Latin American feminist genealogies, this article analyzes them from the axes of anonymity, performance and space, to highlight the political potential that its use had as a collective practice. Methodologically, a bibliographic review has been made, in addition to an analysis of the mentions of the tapadas in Flora Tristán’s travel diary through Peru, Peregrinaciones de una paria (1838), who is the only female counterpart that records the practice during its validity, according to whose observation “There is no place on earth where women are freer” the article is conducted and from which it resumes its homonymous title.